2010
DOI: 10.1111/j.1600-6143.2010.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration of Regenerative Response Improves the Outcome of Rat with Massive Hepatectomy

Abstract: Small residual liver volume after massive hepatectomy or partial liver transplantation is a major cause of subsequent liver dysfunction. We hypothesize that the abrupt regenerative response of small remnant liver is responsible for subsequent deleterious outcome. To slow down the regenerative speed, NS-398 (ERK1/2 inhibitor) or PD98059 (selective MEK inhibitor) was administered after 70% or 90% partial hepatectomy (PH). The effects of regenerative speed on liver morphology, portal pressure and survival were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 29 publications
3
72
1
1
Order By: Relevance
“…Similarly, patients with a higher estimated RLL more often recovered liver function at POD7, again suggesting the positive influence of a higher remnant, but more so emphasizing the importance of accurate estimation of the remnant preoperatively with state of the art imaging modalities and software (and by an experienced radiologist), and choosing donors with good RLL volumes. Contrary to findings in other studies (20,32,37) [14,18]), and also during the first month, (RLL/TLV ranged from 64% to 89% [25,30,33,49], and mean liver growth from 115% to 181% [14,25,27]). After the initial month, the rate of regeneration slowed down, RLL/TLV reaching 74-80% (33,38,40,53), 72-96% (17,23,29,31,37,46,(51)(52), and 80-97% (16,23,26,29,31,33,40,53) in the first 3 months, 6 months, and 1 year, respectively, after donor right hepatectomy.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, patients with a higher estimated RLL more often recovered liver function at POD7, again suggesting the positive influence of a higher remnant, but more so emphasizing the importance of accurate estimation of the remnant preoperatively with state of the art imaging modalities and software (and by an experienced radiologist), and choosing donors with good RLL volumes. Contrary to findings in other studies (20,32,37) [14,18]), and also during the first month, (RLL/TLV ranged from 64% to 89% [25,30,33,49], and mean liver growth from 115% to 181% [14,25,27]). After the initial month, the rate of regeneration slowed down, RLL/TLV reaching 74-80% (33,38,40,53), 72-96% (17,23,29,31,37,46,(51)(52), and 80-97% (16,23,26,29,31,33,40,53) in the first 3 months, 6 months, and 1 year, respectively, after donor right hepatectomy.…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, it follows that the smaller the graft, the greater is the proportion of hepatocytes entering the replicative process to form these islands, decreasing the amount of functional liver tissue available even as gross mass is restored (44). This helps explain why multiple studies, including our own, have reported that functional regeneration does not correlate with volumetric regeneration during the early stages of liver regrowth (4,5,(51)(52)(53)(54) and that strategies that decelerate regeneration can actually lead to better preservation of normal hepatic microarchitecture and improved survival during the regenerative process (43).…”
Section: Discussionmentioning
confidence: 78%
“…While some authors argue that SFSS arises primarily due to the failure of a partial liver to regenerate (41,42), other groups have made observations to the contrary. In the clinical setting, good restoration of hepatic size on computer tomographic volumetry is observed in patients who simultaneously demonstrate clinical signs of liver insufficiency (43,44), and small grafts have been shown to have greater regenerative capacity compared with larger ones (45). In our own preclinical experience, we have consistently observed a significantly greater increase in mass and TK activity among failing SFS grafts versus those with initial good function, in particular those treated with measures to reduce PVF and suppress regeneration (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The liver regeneration that occurs after hepatectomy rapidly replaces the hepatocytic mass removed, limiting ALF to three or four days 10,13,14 . During this period, in animal models of ALF, there should be a large number of deaths, which is characteristic of ALF; however, the mortality rate in the early hours cannot be excessive, or else it shortens the Defining the anesthetic regimen for surgical procedures in animals can be a challenge.…”
Section: Discussionmentioning
confidence: 99%